2014
DOI: 10.1016/j.biocon.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forest fragments contribute to species richness in adjacent oil palm plantations

Abstract: In Southeast Asia, large-scale conversion of rainforest to oil palm plantations is one of the major causes of biodiversity declines. Recommendations for reducing species losses and increasing the sustainability of palm oil production advocate the retention of natural forest patches within plantations, but there is little evidence for the effectiveness of this strategy. Here, we examine to what extent rainforest remnants with different characteristics contribute to biodiversity within surrounding plantations. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 60 publications
7
66
2
2
Order By: Relevance
“…Previous studies of invertebrates in Sabah indicated that even relatively small VJRs supported populations of forest-dependent species that would not otherwise be able to persist in the agricultural landscape (Benedick et al 2006 ;Hill et al 2011 ). This contrasts with data indicating that HCVs supported few species of forest birds or ants (Edwards et al 2010 ;Lucey et al 2014 ). These studies suggest a qualitative difference in the conservation value of these different types of forest fragment, but direct comparisons have previously been lacking.…”
Section: Introductioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Previous studies of invertebrates in Sabah indicated that even relatively small VJRs supported populations of forest-dependent species that would not otherwise be able to persist in the agricultural landscape (Benedick et al 2006 ;Hill et al 2011 ). This contrasts with data indicating that HCVs supported few species of forest birds or ants (Edwards et al 2010 ;Lucey et al 2014 ). These studies suggest a qualitative difference in the conservation value of these different types of forest fragment, but direct comparisons have previously been lacking.…”
Section: Introductioncontrasting
confidence: 55%
“…In contrast to oil palm, we found that VJRs supported 78 % of the species sampled at control sites (calculated from data in Fig. 3 ), supporting previous evidence that such forest remnants make an important contribution to biodiversity within agricultural landscapes (Benedick et al 2006 ;Lucey et al 2014 ). However, HCVs supported only 22 % of the species recorded at control sites, which is only slightly higher than the proportion of forest species recorded within the oil palm itself (19 %; Fayle et al 2010 ).…”
Section: Discussionmentioning
confidence: 32%
See 2 more Smart Citations
“…Preserving natural forest within plantation-dominated landscapes can help reduce carbon emissions by limiting deforestation and help maintain tropical ecosystem functioning that is otherwise lost in an oil palm monoculture (Larsen et al, 2005;Memmott et al, 2007;Morris, 2010). Because protected areas can only safeguard biodiversity if animals are able to move between forest patches through dedicated habitat corridors (Bruford et al, 2010;Gregory et al, 2014), riparian buffers can support some terrestrial biodiversity by serving as sanctuaries for forest-dependent species (Evans et al, 2017;Lucey et al, 2014;Turner & Corlett, 1996) and by offering continuous habitat pathways between fragments of forest matrix. Maintaining natural riparian cover along tropical rivers may help protect aquatic biodiversity by reducing the severity of impacts on freshwater ecosystems from otherwise total conversion of floodplain forest (Chellaiah & Yule, 2018;Mander et al, 2005;Naiman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%